Application of Hyaluronic Acid in the Preparation of Lithium-Sulfur Batteries
Hyaluronic acid (HA) is a catalyst, through adsorption and catalytic synergistic action, the polysulfide shuttle effect and slow sulfur conversion kinetics of lithium-sulfur batteries under electrolyte lean conditions, and achieves the performance of lithium-sulfur batteries with high energy density and long cycle life.
Patent Information
- Application Number
- CN202510592095.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-09
- Publication Date
- 2025-08-05
- Estimated Expiration
- 2045-05-09
AI Technical Summary
In the existing lithium-sulfur battery, the polysulfide shuttle effect is severe, the sulfur conversion kinetics are slow, and the electrolyte is insufficient contact, resulting in low battery capacity and poor cycle life. The catalytic effect of traditional catalysts under the electrolyte is poor.
Hyaluronic acid (HA) is used as a catalyst to adsorb the electrolyte through its unique double helix structure and catalyze the reversible transformation of polysulfides, promote lithium ion transmission, form a reaction microenvironment with sufficient local electrolyte, and reduce the Li2S nucleation overpotential.
Under the condition of lean electrolyte, the initial capacity, rate performance and cycle life of the lithium-sulfur battery are significantly improved, and high energy density and long cycle life are achieved. The area capacity of the soft-pack battery reaches 11.76 mAh cm-2, the energy density reaches 409 Wh·kg-1, and the 1.5Ah soft-pack battery can drive the drone for 20 minutes.
Smart Images

Figure CN120149493B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium-sulfur batteries, and in particular to the application of hyaluronic acid in the preparation of lithium-sulfur batteries. Background Art
[0002] With the increasing demand for low-cost, high-energy-density energy storage technologies, lithium-sulfur batteries have become a popular choice due to their huge economic advantages and satisfactory theoretical energy density (volume energy density: 2800 Wh L -1 , mass density: 2600 Whkg -1 ), becoming an extremely attractive next-generation lithium secondary battery.
[0003] At present, lithium-sulfur batteries are mainly prepared by adding excess electrolyte (E / S ratio> 20 μL mg -1 ) to improve battery conductivity and enhance lithium ion transmission efficiency. The electrolyte accounts for more than half of the total mass and total cost of the battery. This will not only limit the actual energy density of the battery, but also limit the mass energy density <100 Wh kg -1 , which also increases the cost of batteries and limits the large-scale application of lithium-sulfur batteries. In order to achieve a lithium-sulfur battery mass energy density exceeding 400 Wh kg -1 The battery's E / S ratio must be <5 μL mg -1 However, a low E / S ratio will seriously affect the already complex lithium-sulfur electrochemical process, making the sulfur conversion reaction involving 16 electrons slower and the ionic conductivity of the cathode decreased, resulting in a low specific capacity of the battery (<1000 mAh g -1 ) and poor cycle life performance (<100 cycles).
[0004] Although current research has proven that the use of electrocatalysts can accelerate the kinetics of sulfur conversion reactions, traditional catalysts do not perform well under lean electrolyte conditions. The reasons are:
[0005] (1) Unlike the abundant electrolyte system, in the lean electrolyte system, a large amount of sulfur is forced to dissolve in a small amount of electrolyte, which greatly increases the concentration of polysulfides in the electrolyte, even reaching the solubility limit of polysulfides. The increase in the concentration of polysulfides in the electrolyte is accompanied by an increase in the viscosity of the electrolyte, which not only slows down the sulfur conversion kinetics but also hinders the transport of lithium ions.
[0006] (2) Driven by a high polysulfide concentration gradient, the shuttle effect of lithium-sulfur batteries is intensified, and polysulfides are more likely to diffuse to the lithium anode and react with it, accelerating the consumption of the electrolyte and shortening the cycle life of the battery.
[0007] (3) When the amount of electrolyte is reduced to an E / S ratio of less than 5.2 μL mg -1When the solubility of polysulfides in the electrolyte reaches its limit, sulfur or Li2S will not be able to be converted into polysulfides and dissolved in the electrolyte. At this time, the sulfur or Li2S accumulated at the cathode cannot undergo electrochemical reactions and becomes dead sulfur that cannot be reused, resulting in a significant reduction in battery capacity. In response to the challenges brought about by the above-mentioned lean electrolyte conditions, it is necessary to develop new catalysts that can simultaneously meet multiple requirements (effectively enriching the electrolyte, promoting ion transport, inhibiting the polysulfide shuttle effect, and preventing electrode surface passivation) under lean electrolyte conditions in order to fully utilize the advantages of high energy density and low cost of lithium-sulfur batteries. Summary of the Invention
[0008] The present invention aims to provide the use of hyaluronic acid as a catalyst in lithium-sulfur batteries to solve technical problems such as high electrolyte ratio and general electrochemical performance of existing lithium-sulfur batteries.
[0009] To achieve the above objectives, the present invention provides the use of hyaluronic acid in the preparation of a lithium-sulfur battery cathode composite material.
[0010] Preferably, the lithium-sulfur battery is a lean electrolyte lithium-sulfur battery, and the lean electrolyte condition is: sulfur loading> 4 mg·cm -2 、Electrolyte / sulfur<5 μL·mg -1 , E / S ratio <5 μL·mg -1 .
[0011] Preferably, hyaluronic acid HA, carbon nanotubes CNT and polyvinylidene fluoride PVDF are first added to 1-methyl-2-pyrrolidone NMP, ultrasonically shaken for 1 hour to make them uniformly dispersed in NMP, and then the CNT-S composite material obtained by compounding CNT and sulfur powder is added, stirred evenly to obtain a slurry, and then the slurry is evenly coated on aluminum foil and vacuum dried to obtain; wherein, the mass ratio of HA, CNT, PVDF, and CNT-S composite material is 0.2~4:14.8~11:5:80, and more preferably 1:14:5:80.
[0012] More preferably, PVDF is prepared into a solution with a mass concentration of 5% using NMP for feeding.
[0013] More preferably, about 1.5 mL of NMP is used per 250 mg of slurry.
[0014] Further preferably, the CNT-S composite material is prepared by the following method: first, CNT and sulfur powder are mixed in a mass ratio of 2:8 and ground for 30 minutes, then dried, cooled, and sieved.
[0015] More preferably, the drying conditions are: drying at 155°C for 8 hours; and passing through a 400 mesh sieve after cooling.
[0016] More preferably, the vacuum drying condition is: vacuum drying at 55°C for 8 hours.
[0017] The present invention provides application of hyaluronic acid in the preparation of a composite cathode for a lithium-sulfur battery.
[0018] Preferably, the lithium-sulfur battery is a lean electrolyte lithium-sulfur battery, and the lean electrolyte condition is: sulfur loading> 4 mg·cm -2 、Electrolyte / sulfur<5 μL·mg -1 , E / S ratio <5 μL·mg -1 .
[0019] Preferably, the composite cathode material made of hyaluronic acid is cut into circular electrodes with a diameter of 14 mm, which is recorded as CNT-S / HA.
[0020] The present invention provides application of hyaluronic acid in the preparation of lithium-sulfur batteries.
[0021] Preferably, the lithium-sulfur battery is a button cell or a soft pack cell.
[0022] Preferably, the lithium-sulfur battery is a lean electrolyte lithium-sulfur battery, and the lean electrolyte condition is: sulfur loading> 4 mg·cm -2 、Electrolyte / sulfur<5 μL·mg -1 , E / S ratio <5 μL·mg -1 .
[0023] Preferably, a composite cathode made of hyaluronic acid is assembled with a separator, a metal lithium anode, and an electrolyte to obtain a lithium-sulfur battery.
[0024] Further preferably, the diaphragm is a Celgard 2400 diaphragm, the electrolyte is obtained by dissolving LiTFSI (lithium bis(trifluoromethanesulfonyl imide)) in a mixed solvent to a concentration of 1.0 mol / L, and then adding lithium nitrate with a mass concentration of 1.0%, and the mixed solvent is obtained by mixing equal volumes of 1,3-dioxolane DOL and ethylene glycol dimethyl ether DME, and adding 1.0% of ).
[0025] The present invention has the following beneficial effects:
[0026] Hyaluronic acid (HA), a natural glycosaminoglycan, is widely used in cosmetic medicine, drug delivery, nutrition and other fields. It has the following excellent structural and performance characteristics: (1) HA is composed of two identical long chains (D-glucuronic acid (D-GLCA) and N-acetyl-D-glucosamine (GLcNAc) disaccharide units arranged alternately), which are randomly curled and coiled to form a double helix structure. This special three-dimensional structure can not only construct a columnar ion transport channel, but also help to lock a large amount of solution; (2) HA has significant antioxidant activity and can scavenge oxygen free radicals in biological systems. Since oxygen and sulfur belong to the same main group in the periodic table, according to the periodic expansion theory, HA can theoretically eliminate sulfur free radicals, thereby inhibiting the shuttle of polysulfides and reducing electrolyte consumption; (3) HA is rich in a large number of hydroxyl functional groups. The hydroxyl groups attract electrolyte molecules through hydrogen bonds, so that the hydroxyl groups in the HA double helix form internal hydrogen bonds with electrolyte molecules, effectively capturing and storing a large amount of electrolyte. Therefore, the applicant speculates that HA can achieve a sufficient electrolyte environment in the microregion close to the hydroxyl group, thereby ensuring sufficient contact between the active material (sulfur / Li2S) and the electrolyte ( Figure 1 ).
[0027] This invention addresses the challenges of polysulfide shuttling, slow sulfur conversion kinetics, and insufficient electrolyte contact in poor-electrolyte lithium-sulfur batteries by innovatively introducing HA as a multifunctional catalyst for the sulfur cathode. Experimental and molecular dynamics simulation results show that HA can firmly adsorb the electrolyte through the intramolecular hydrogen bonds in its double-helical cavity structure, ensuring full contact between the electrolyte and the electrode surface and providing a local reaction microenvironment with sufficient electrolyte, thus forming a local reaction microregion with sufficient electrolyte. At the same time, HA adsorbs and catalyzes the reversible transformation of polysulfides through the N site, catalyzing sulfur redox reactions and reducing the Li2S nucleation overpotential. The unique double-helical structure of HA also promotes the + The CNT-S / HA cathode (about 80 wt% sulfur loading) exhibited a good initial capacity (1493 mAh·g -1 , 0.2 C), high rate performance (714 mAh·g -1 , 5 C) and long cycle life (capacity retention rate exceeds 69.8% after 1500 cycles, and the single-cycle attenuation rate is only 0.02%). -2 , E / S ratio was 3 μL·mg -1 Under the condition of poor electrolyte, the areal capacity of lithium-sulfur soft pack battery reaches 11.76 mAh cm -2 , the energy density can reach 409 Wh·kg -1, and the 1.5Ah soft-pack battery can drive the drone for 20 minutes (four times longer than traditional lithium batteries).
[0028] In summary, this invention applies the liquid-retaining, antioxidant and double-helix properties of HA to lithium-sulfur batteries for the first time, breaking through the bottleneck of electrolyte-poor lithium-sulfur batteries through the synergistic adsorption and catalysis, providing a new strategy for the design of high-energy-density energy storage devices, and opening up a unique path for the development of natural moisturizing materials in the next generation of energy storage devices.
[0029] In addition to the above-described objects, features and advantages, the present invention has other objects, features and advantages. The present invention will be further described in detail below with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The accompanying drawings, which constitute part of this application, are intended to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are intended to explain the present invention and do not constitute an undue limitation of the present invention. In the accompanying drawings:
[0031] Figure 1 This is a schematic diagram of hyaluronic acid promoting sulfur conversion;
[0032] Figure 2 These are photos showing the mass changes of HA+electrolyte and CNT+electrolyte over time.
[0033] Figure 3 This is a photograph of a standard solution of 0.1-0.9 mL of DOL / DME dissolved in 2 mL of ethanol.
[0034] Figure 4 UV-visible absorption spectra of DOL / DME standard solutions with different concentrations were tested, including (a) UV-visible absorption spectrum of standard solution and (b) linear fitting between absorbance and DOL / DME volume.
[0035] Figure 5 It is a quantitative comparison of the enrichment ability of HA and CNT for electrolyte, including photos of (a) HA and (b) CNT immersed in DOL / DME solvent, (c) UV-visible absorption spectra of DOL / DME solvent adsorbed by HA and CNT, respectively, and the volume of electrolyte adsorbed by both.
[0036] Figure 6 are the contact angles of DOL / DME droplets on (a) CNT-S / HA cathode surface and (b) CNT-S cathode surface.
[0037] Figure 7 Raman spectra of the local solvent environment on the surface of (a) HA and (b) D-GLCA / GLcNAc materials changing with time.
[0038] Figure 8 (a) Structural model and (b) energetics of DOL / DME adsorption by HA and D-GLCA / GLcNAc.
[0039] Figure 9 These are photos of the color changes of Li2S6 adsorbed on different materials.
[0040] Figure 10 It is the adsorption energies of S8, Li2S8, Li2S6, Li2S4, Li2S2 and Li2S on Gh-HA and Gh substrates, as well as the adsorption structure model of Li2S6 on Gh-HA and Gh substrates.
[0041] Figure 11 Structural models of S8, Li2S8, Li2S4, Li2S2, and Li2S adsorbed on (a) Gh-HA or (b) Gh substrates.
[0042] Figure 12 CV curves of the first four cycles of different cathodes under sufficient electrolyte conditions: (a) CNT-S / HA, (b) CNT-S.
[0043] Figure 13 is the lean electrolyte condition (E / S=5 μL mg -1 CV curves under . (a) Comparison of CV curves of CNT-S / HA and CNT-S in the third cycle of cathode. (b) CV curves of CNT-S / HA and (c) CNT-S in the first four cycles.
[0044] Figure 14 This is a comparison of the CV curves of the third cycle of CNT-S / HA and CNT-S cathode under sufficient electrolyte conditions.
[0045] Figure 15 is the Tafel slope analysis, where (ac) is based on Figure 14 The Tafel slopes of the cathode process of the CV curves correspond to the reduction peak (a) i, reduction peak (b) and oxidation peak iii (c), (df) based on Figure 13 The Tafel slopes of the cathode process of the CV curve in (a) correspond to the reduction peak i (d), reduction peak ii (e) and oxidation peak iii (f), respectively.
[0046] Figure 16 The CV curves of the symmetrical cell with CNT / HA and CNT cathode were obtained at a scan rate of 10 mV s. -1 .
[0047] Figure 17Steady-state discharge curves of Li2S nucleation for (a) CNT / HA and (b) CNT cathodes under sufficient electrolyte conditions, and steady-state discharge curves of Li2S nucleation for (c) CNT / HA and (d) CNT cathodes under poor electrolyte conditions.
[0048] Figure 18 CV curves of (a) CNT-S / HA cathode, (b) CNT-S cathode, and (c) CNT-S / D-GLCA / GLcNAc cathode at different scan rates.
[0049] Figure 19 is the NTR value of the two cathodes.
[0050] Figure 20 EIS curve analysis, including EIS curves of (a) CNT-S / HA and (b) CNT-S cathode before and after 10 cycles. (c) R of CNT-S / HA cathode and CNT-S cathode before and after 10 cycles ct .
[0051] Figure 21 In situ UV-visible absorption spectra of (a) CNT / HA and (b) CNT cathode.
[0052] Figure 22 During the discharge process, sulfur species (S8 2- (~492 nm), S6 2- (~475 nm), S4 2- (~420 nm) and In situ UV-visible contour images (~617 nm) of (a) CNT / HA cathode, (b) CNT cathode.
[0053] Figure 23 CNT-S / HA, CNT-S and CNT-S / D-GLCA / GLcNAc cathode Ip / v 0.5 The relationship between (a) I v1 , (b) I v2 , (c) I p .
[0054] Figure 24 GITT curves of (a) CNT-S / HA, (b) CNT-S, and (c) CNT-S / D-GLCA / GLcNAc.
[0055] Figure 25 are the E1, E2, and E3 values in GITT.
[0056] Figure 26 The D of the three cathodes during the charge and discharge process Li + .
[0057] Figure 27 (a) Models of HA and D-GLCA / GLcNAc based on MD calculations and (b) the corresponding D Li + value.
[0058] Figure 28 It is the rate performance of lithium-sulfur batteries with different mass ratios of HA added.
[0059] Figure 29 It is the rate performance of CNT-S / HA and CNT-S.
[0060] Figure 30 (a) The charge-discharge curves of CNT-S / HA and CNT-S at 0.2 C, and the constant current charge-discharge curves of (b) CNT-S / HA and (c) CNT-S cathode at different rates.
[0061] Figure 31 It is the 1 C long cycle performance of CNT-S / HA and CNT-S.
[0062] Figure 32 (a) High sulfur loading of 8 mg cm -2 , E / S ratio was 5 μL mg -1 Cycling performance of lithium-sulfur batteries, (b) constant current charge-discharge curves of (a), (c) high sulfur loading of 8 mg cm -2 (double-sided), E / S ratio of 3 μL mg -1 Cycling performance of 1.5 Ah soft-pack batteries at 0.1 C, (d) Performance comparison of CNT-S / HA cathode with other cathode systems. DETAILED DESCRIPTION
[0063] The embodiments of the present invention are described in detail below with reference to the accompanying drawings. However, the present invention can be implemented in many different ways as defined and covered by the claims.
[0064] 1. Experimental drugs and instruments (Tables 1-3)
[0065] Table 1. Main experimental drugs
[0066]
[0067] Table 2. Main gases used
[0068]
[0069] Table 3. Main experimental instruments
[0070]
[0071] 2. Material preparation
[0072] (1) Preparation of CNT-S composite materials
[0073] The CNT-S composite was prepared using the classic melt-diffusion method. First, CNTs and sulfur powder at a mass ratio of 2:8 were ground in a mortar for 30 minutes. The mixture was then transferred to a weighing bottle and heated in an oven at 155°C for 8 hours. The cooled composite was then sieved through a 400-mesh sieve to obtain the CNT-S composite.
[0074] (2) Preparation of cathode composite materials.
[0075] PVDF powder and NMP were mixed and stirred to obtain a 5 wt% PVDF solution (mass ratio of 1:19). HA, CNT, and a 5 wt% PVDF solution were then added to a weighing bottle at a mass ratio of 1:14:100. The solution was then ultrasonically shaken for 1 hour to uniformly disperse the mixture. A CNT-S composite (CNT-S to HA mass ratio of 1:80) was then added to the weighing bottle and mixed with an appropriate amount of NMP. The resulting slurry was evenly coated on aluminum foil and vacuum-dried at 55°C for 8 hours. The dried electrode was sliced into 14 mm diameter circular pieces using a microtome to obtain a CNT / S-HA composite cathode. The preparation methods for the CNT-S and CNT-S / D-GLCA / GLcNAc composite cathodes were identical to those for the CNT / S-HA composite cathode, except that the HA was replaced with CNT or D-GLCA / GLcNAc (D-glucuronic acid / N-acetylglucosamine).
[0076] 3. Battery assembly and testing
[0077] (1) Battery assembly
[0078] The assembly of CR2025 button cells needs to be carried out in a highly pure glove box environment (water and oxygen content are both <0.1 ppm). Both button cells and soft-pack cells are composed of CNT-S / HA composite cathodes, separators, metal lithium anodes and electrolytes, but the assembly processes are slightly different. For button cells, first place the prepared electrode sheet into the cathode shell, and use a pipette to add an appropriate amount of electrolyte drop by drop. After placing the separator, continue to add an appropriate amount of electrolyte, then place the lithium sheet, gasket and shrapnel on the separator, and finally cover the anode shell and seal it through a button packaging machine. In the assembly process of soft-pack cells, the applicant uses a double-sided coated CNT-S / HA composite cathode. First, the CNT-S / HA composite cathode, metal lithium and separator are stacked and embedded in a pre-formed aluminum-plastic film bag, leaving space for liquid injection, and sealed using heat sealing technology; then, liquid is injected with a pipette and vacuum packaged. The sulfur surface loading of the cathode of a conventional button cell is about 1 mg cm-2 , the E / S ratio was maintained at 20 μL mg -1 Under high sulfur loading and lean electrolyte conditions, the sulfur loading at the cathode is approximately 8 mg cm -2 , the E / S ratio is about 5 μL mg -1 The sulfur loading on a single surface of the soft pack battery is 8 mg cm -2 , the E / S ratio was controlled at 3 μL mg -1 .
[0079] (2) Battery test
[0080] All assembled batteries were left at room temperature for 12 hours and then tested in a 30°C constant temperature chamber. The battery rate performance and long cycle performance tests were conducted using the constant current charge and discharge mode of the Xinwei battery test cabinet, with the operating voltage window set to 1.6-2.8 V (vs. Li / Li + ), the specific capacity is calculated based on the sulfur content in the cathode material. CV and EIS tests were performed using a CHI 760 electrochemical workstation: the CV test voltage range was consistent with the charge-discharge test voltage, and the scan rate was set to 0.1-0.25 mV s -1 The EIS test was performed under open circuit voltage, with a frequency range of 100 kHz to 0.01 mHz and an AC amplitude of 5 mV.
[0081] 4. Experimental methods
[0082] (1) Visualization experiment of polysulfide adsorption
[0083] The same mass of HA, CNT / HA or CNT was added into 2.0 mL of 0.2 mmol L -1 The digital photos of the samples after 48 h of static adsorption were taken to evaluate the adsorption capacity of different materials for polysulfides. -1 The Li2S6 solution was prepared by stirring Li2S and sulfur powder (molar ratio of 1:5) in a DOL / DME mixed solution (v:v = 1:1) at 60 °C for 24 h.
[0084] (2) Li based on CV test + Diffusion coefficient and nucleation factor
[0085] At 1.6-2.8 V (vs. Li / Li + ) voltage range, 0.1 to 0.25 mV s -1 The CV experiment was carried out at a scan rate of 100 nm to obtain the CV curves at different scan rates. The Li+ Diffusion coefficient (D Li + ) to make an estimate.
[0086] (1)
[0087] Among them I p is the peak current, n is the number of electron transfers, S is the electrode geometric area, D is Li + Diffusion coefficient, C is the Li + concentration, and v is the scan rate.
[0088] The nucleation factor (NTR) can be calculated according to formulas (2 and 3).
[0089] (2)
[0090] (3)
[0091] Among them C e is the amount of electron transferred per gram, A t is the integrated area of peak i or peak ii, v is the scanning rate, C e1 and C e2 are the C of peak i and peak ii, respectively. e value.
[0092] (3) Constant current intermittent titration technology test and its Li + Calculation of diffusion coefficient
[0093] The GITT test was conducted at room temperature using a Xinwei battery test system. Within the voltage range of 1.6-2.8 V (vs. Li / Li⁺), a constant current pulse of 0.05 C was applied alternately for 20 minutes, followed by a 2-hour no-current standstill cycle, and this cycle was repeated until a complete charge and discharge cycle was completed. The cathode D Li + Use formula (4) to calculate:
[0094] (4)
[0095] Where τ is the constant current pulse time, m B 、V M and M B are the mass, molar volume and molar mass of the active material respectively, S is the area of the electrode, ΔE s is the total voltage change caused by the pulse, ΔE t It is the voltage change during constant current charge and discharge process.
[0096] (4) Assembly and measurement of symmetrical batteries
[0097] The button cell cathodes used for the symmetrical battery test were both sulfur-free CNT / HA cathodes. The preparation method of the CNT / HA cathode was similar to that of the CNT-S / HA cathode, with the only difference being that no CNT-S composite material was added. CNT (94 wt%), HA (1 wt%), and PVDF (5 wt%) were added to the NMP solution and stirred thoroughly to form a slurry; the resulting slurry was coated on aluminum foil and dried at 55°C for 8 h, and then the dried electrode was cut into discs with a diameter of 14 mm. CNT / HA cathodes were used as cathodes and cathodes during battery assembly, with a concentration of 0.2 mol L -1 Li2S6 solution was used as the electrolyte, and the amount of electrolyte was 20 μL on each side of the cathode and anode. -1 The scan rate was between -1.0 and 1.0 V (vs. Li / Li + ) voltage range for CV test.
[0098] (5) Li2S deposition experiment
[0099] The cathode preparation method for the coin cell used for the Li2S deposition test is the same as that of the CNT / HA cathode composite material for the symmetric cell, but the current collector used is carbon cloth instead of aluminum foil. During the assembly process, CNT / HA is used as the cathode, Celgard 2400 is used as the separator, and metallic lithium is used as the anode. 20 μL of 0.25 mol L -1 Li2S8 solution was prepared by adding 20 μL of tetraethylene glycol dimethyl ether (TEGDME) to the lithium anode. The assembled button cell was first charged to 2.06 V at a constant current of 0.115 mA using a Xinwei battery test system. Then, the Li2S nucleation test was performed at a constant potential of 2.04 V on a CHI 760E electrochemical workstation. When the current was less than 1 × 10 -5 The test is terminated at A, and the current-time (it) curve is obtained. The Li2S8 solution is prepared by heating and stirring Li2S and sulfur powder in TEGDME solvent.
[0100] (6) Theoretical calculation
[0101] All molecular dynamics simulations were performed using the MaterialsStudio2020 software package. The present invention selects the COMPASSI force field for simulation to ensure the accuracy and reliability of the calculation results. The applicant calculated the adsorption energy of HA molecules and polysulfides and HA and electrolyte molecules. The process includes system configuration optimization and energy minimization. At the beginning of the simulation, HA molecules and polysulfides and HA and electrolyte molecules were randomly distributed in the simulation box, and then energy minimization was performed, and the NVT ensemble was used to perform a 500 ps equilibrium simulation at 300 K to ensure that the system reached thermodynamic equilibrium. The applicant calculated the total energy before and after adsorption through the Forcite module in MaterialsStudio, and then calculated the adsorption energy. Adsorption energy (E ads ) is calculated using formula (5).
[0102] (5)
[0103] Among them E Total Represents the total energy of the system, E a represents the energy of the matrix, E b represents the energy of the adsorbent.
[0104] D Li + The diffusion coefficient D is obtained by analyzing the root mean square displacement (MSD) of HA molecules in the electrolyte. The simulation was performed using the NPT ensemble at 300K and 1 atm, with a total duration of 500 ps and a time step of 1 s. Li + Calculated by Einstein equation (Formula 6):
[0105] (6)
[0106] Among them, D Li + represents the diffusion coefficient, represents the position of the particle at time t, represents the initial position of the particle, N a Indicates the number of lithium ions.
[0107] 5. In-situ characterization test
[0108] A carbon nanotube / hyaluronic acid (CNT / HA) modified glassy carbon electrode was used as the working electrode, a platinum wire electrode was used as the counter electrode, and the electrolyte was 0.1 mmol L -1 Li2S8 solution (prepared by dissolving Li2S powder and sulfur powder in DMSO at a stoichiometric ratio of 1:7 and stirring for 48 h) was electrochemically tested on a Shanghai Chenhua CHI 760E electrochemical workstation at 0.1 mV s -1The discharge was carried out at a rate of 1.5 volts, and absorbance data were collected at every 0.1 V potential interval using a Shimadzu UV-3600 UV-visible spectrophotometer. A control experiment was performed using a CNT-modified glassy carbon electrode.
[0109] 6. Experimental Results and Discussion
[0110] 6.1 Adsorption of HA on electrolyte and polysulfides
[0111] In order to explore the enrichment ability of HA in electrolyte, the applicant added the same mass of HA and CNT into 1 g of electrolyte and measured the changes in the mass of the electrolyte over different time periods. Figure 2 As shown in the figure, the weight of the two bottles gradually decreased over time due to electrolyte volatilization. After 48 hours, the mass change of the bottle with CNTs was 545.9 mg, while the mass change of the bottle with HA was only 479.3 mg. This shows that the bottle containing HA has a lower electrolyte consumption rate than the bottle containing CNTs, which directly indicates that HA has a better electrolyte enrichment ability than CNTs.
[0112] In addition to the macroscopic mass change, the enrichment capacity of different materials for the electrolyte was quantitatively evaluated by UV-visible absorption spectroscopy. Before quantitative comparison, a standard relationship between absorbance and solvent volume must first be established. According to the Lambert-Beer law (A = b × ε × c) (A is the UV-visible absorbance of the sample, ε is the molar absorptivity, b is the thickness of the absorption layer (fixed at 1 cm), and c is the solution concentration), A is proportional to c. Therefore, 0.1-0.9 mL DOL / DME (v:v=1:1) was dissolved in 2 mL ethanol to prepare standard solutions (see Figure 3 ). UV-visible absorption spectra of DOL / DME standard solutions with different concentrations were tested, such as Figure 4 As shown in Figure a, two absorption peaks are observed at about 200 and 280 nm, respectively. These two characteristic peaks are attributed to the transition from electrons to antibonding molecules in DOL / DME. Based on the strong absorption peak around 200 nm, the applicant established a standard curve of absorbance and concentration (see Figure 4 Middle b).
[0113] In order to quantitatively compare the enrichment ability of HA and CNT for electrolyte, 12 g HA ( Figure 5 a) or CNT ( Figure 5 b) Immerse in 1.5 mL of DOL / DME solution (DOL / DME is the main component of the electrolyte) for 12 h. After the HA and CNTs have completely absorbed the electrolyte, 0.5 mL of the supernatant is removed and mixed with 2 mL of ethanol for UV-visible absorption spectroscopy. Figure 5 The results in Figure c show that the absorbance of the solution after HA adsorption is lower than that after CNT adsorption. Substituting the respective absorbance values into Figure 4 From the standard curve in b, we can calculate that the amount of HA adsorbed per unit mass of electrolyte is 74.8 μL mg –1 , which is much larger than the electrolyte adsorption capacity of CNT 30.8 μL mg –1 , which indicates that there is a stronger adsorption effect between HA and DOL / DME. Figure 6 Contact angle experiments further showed that the electrolyte contact angle of the HA-modified cathode surface (4°) was lower than that of the CNT cathode surface (31°), indicating that the HA-modified cathode surface exhibited better wettability due to the electrolyte enrichment ability of HA.
[0114] In order to investigate the adsorption of HA on electrolyte in micro-areas and its adsorption mechanism, the same volume of DOL / DME solution was dripped onto the surface of the same mass of HA (with double helical structure) and its monomer mixture (D-GLCA / GLcNAc, without double helical structure). Raman spectra of the electrolyte on the surfaces of the two samples were collected at different times. Figure 7 As shown, approximately 2900 cm –1 The signal at is attributed to DOL and DME molecules. Over time, the signal gradually weakens due to the volatilization of DOL / DME from the surface. The DOL / DME signal persists longer on the HA surface (approximately 25 minutes) than on D-GLCA / GLcNAc (approximately 10 minutes), indicating that the double helix of HA facilitates electrolyte enrichment.
[0115] The above Raman spectroscopy experiments have proved that the ability of HA to enrich the electrolyte is due to its double helix structure. In order to further study the mechanism of double helix structure enrichment of electrolyte, the applicant conducted theoretical calculations on the interaction between the two materials and DOL / DME. From the theoretical calculation results ( Figure 8 ) can be found that DOL and DME molecules are preferentially adsorbed in the helical cavity of HA, with a lower adsorption energy (E ads-DOL =-10.46 eV, E ads-DME =-18.11 eV), and a large number of intramolecular hydrogen bonds were formed between the O atoms of DOL / DME and the internal hydroxyl groups of HA. In contrast, the adsorption of DOL and DME on D-GLCA / GLcNAc requires more energy (E ads-DOL =-2.38 eV, E ads-DME=-6.04 eV). Both theoretical calculations and experiments have demonstrated that the abundant hydroxyl groups within HA can better capture electrolyte molecules through intramolecular hydrogen bonding interactions, thereby maintaining sufficient electrolyte contact between the active material and the microregion to support sulfur redox reactions.
[0116] 6.2 Catalytic Ability of HA on Sulfur Conversion Kinetics
[0117] Adsorption is a prerequisite for subsequent catalytic reactions. Therefore, before verifying whether HA promotes the sulfur conversion process, the applicant needs to confirm whether HA has a good adsorption effect on polysulfides. Visual adsorption experiments are effective evidence to prove the adsorption capacity of HA for polysulfides. In the experiment, 6 g of HA, CNT / HA or CNT were added to 2.0 mL of 0.2 mmol / L -1 Li2S6 solution. Figure 9 As shown in the figure, after 48 h of static adsorption, the color of the Li2S6 solution with the addition of HA and CNT / HA became significantly lighter than that of the solution with only CNT added, indicating that HA has a good adsorption effect on Li2S6.
[0118] From a theoretical perspective, molecular dynamics simulations were used to further understand the adsorption behavior and quantify the adsorption energies (E) of different sulfur species (S8, Li2S8, Li2S6, Li2S4, Li2S2, and Li2S) on different materials. ads ). Figure 10 and Figure 11 This is a side view of the optimized model of different sulfur species on graphene (Gh) and HA-Gh. The figure shows that polysulfides are enriched at the N sites of the HA helical cavity and form Li···N bonds, which endows HA with a stronger adsorption capacity for sulfur species. From an energetic perspective, the adsorption energies of HA for S8, Li2S8, Li2S6, Li2S4, Li2S2, and Li2S are -3.44, -5.18, -5.02, -4.44, -3.94, and -4.31 eV, respectively, significantly lower than their adsorption energies on Gh substrates, which are 6.76, 4.99, 4.96, 5.19, 4.71, and 4.25 eV, respectively. This difference highlights the adsorption advantages of HA's unique N sites and double helical structure.
[0119] To explore the catalytic performance of HA on solid-liquid-solid sulfur redox kinetics, the applicant tested the CV curves of CNT-S / HA and CNT-S cathodes under sufficient electrolyte and lean electrolyte conditions. Figure 12 and Figure 13As shown in the figure, the CV curves of the CNT-S / HA cathode show a higher degree of overlap than the CNT-S cathode, regardless of whether the electrolyte is sufficient or poor, indicating that it has better cycle stability. Figure 14 and Figure 13 In a), it was found that, theoretically, the reduction peak (peak i) in the high potential region corresponds to the conversion of sulfur (S8) to soluble long-chain polysulfides (Li2S n , 4 ≤ n < 8), while the reduction peak (peak ii) in the low potential region is related to the transformation of long-chain polysulfides to short-chain polysulfides (Li2S2 and Li2S); at the same time, two obvious oxidation peaks (peak iii and peak iv) correspond to the reverse conversion of short-chain polysulfides to long-chain polysulfides and the final regeneration of elemental sulfur. Compared with the CNT-S cathode, the CNT-S / HA cathode exhibits a higher peak current and a smaller polarization voltage difference (ΔV). These results indicate that HA significantly accelerates the kinetics of sulfur redox reactions, especially under lean electrolyte conditions. Under lean electrolyte conditions, the CNT-S cathode battery cannot even maintain stable cycling, but the CV curve of the CNT-S / HA cathode battery can maintain a profile similar to that under sufficient electrolyte conditions.
[0120] The Tafel slope was quantitatively analyzed ( Figure 15 ) It can be seen that for the reaction of S8 to Li2S4, the CNT-S / HA cathode exhibits a 49 mV dec -1 (sufficient electrolyte) and 53 mV dec -1 The lowest Tafel slope for the reaction of Li2S4 to Li2S is 16 mV dec. -1 (sufficient electrolyte) and 22 mV dec -1 (poor electrolyte); the Tafel slope of Li2S oxidation to Li2S8 is only 75 mV dec -1 (sufficient electrolyte) and 101 mV dec -1 Regardless of the reaction process, the CNT-S / HA cathode exhibits a Tafel slope much smaller than that of the CNT-S cathode, further verifying that HA comprehensively accelerates the redox kinetics of sulfur.
[0121] In addition to CV and Tafel slope, symmetric cell tests can also be used to demonstrate the ability of HA to accelerate the liquid-liquid conversion kinetics of polysulfides. Figure 16It was found that the CNT / HA cathode had a higher current response than the CNT cathode, confirming that HA accelerated the liquid-liquid conversion kinetics of polysulfides. However, the rate-determining step in the discharge process is the liquid-solid phase transition from liquid polysulfides to solid Li2S2 / Li2S. In order to evaluate the effect of HA on the liquid-solid conversion of polysulfides, Li2S nucleation experiments were carried out under sufficient and lean electrolyte conditions. Figure 17 It can be seen from the IT curves in Figures a and b that the CNT / HA cathode only takes 1633 s to reach the peak current, while the CNT cathode takes 6400 s. According to Faraday's law, the Li2S deposition capacity of CNT / HA is calculated to be 383.4 mAh g -1 , much higher than the 294.4 mAh g of CNT-S. -1 The above results show that HA significantly reduces the overpotential of Li2S nucleation and accelerates the nucleation rate of Li2S. Figure 17 In (c, d), the CNT / HA cathode also exhibits faster response, higher current intensity, and larger Li2S deposition capacity, indicating that HA can successfully reduce the nucleation energy barrier under lean electrolyte conditions and can quickly convert more polysulfides into Li2S, showing better catalytic performance.
[0122] In order to quantitatively describe the extent of liquid-solid conversion of polysulfides, the CV curves at different scan rates ( Figure 18 ), the applicant calculated the nucleation factors of the two cathodes. Figure 19 The results show that the NTR value of the CNT-S / HA cathode is about 2.83, which is close to the theoretical value of Li2S4 converted to Li2S (NTR=3), indicating that Li2S4 can undergo rapid liquid-solid conversion on CNT-S / HA. In contrast, the NTR value of the CNT-S cathode is <2.22, and it decreases rapidly with increasing scan rate, indicating that the liquid-solid conversion kinetics is relatively slow in the absence of HA. The above results demonstrate that HA can effectively catalyze sulfur conversion and accelerate the liquid-solid conversion kinetics of polysulfides. In summary, compared with the CNT-S cathode, the CNT-S / HA cathode significantly accelerates the solid-liquid-solid sulfur conversion kinetics, which may be related to the introduction of HA to effectively promote charge transport inside the cathode. According to Figure 20 The EIS curve analysis results show that the CNT-S / HA cathode battery after cycling shows a smaller R ct , this phenomenon confirms the applicant's conjecture.
[0123] In addition, the applicant also used in situ UV-visible absorption spectroscopy to explore the HA-catalyzed polysulfide conversion at the microscopic level. The absorbance data at each 0.1 V potential interval were collected using a Shimadzu UV-3600 UV-visible spectrophotometer. At different discharge depths, the applicant collected UV-visible spectra of different sulfur species on two cathode surfaces (i.e., CNT / HA and CNT). Figure 21 ). 2- (492 nm), S6 2- (475 nm), S4 2- (420 nm) and The absorbance was normalized to 617 nm and plotted as a contour plot ( Figure 22 ). On both cathodes, it was found that as the battery discharge began, S8 2- 、S6 2- and S4 2- The absorbance gradually decreased, and The absorbance of ⁻ increases, indicating that high-order polysulfides are converted to low-order polysulfides. The absorbance change on CNT / HA is greater than that on CNT, indicating that CNT / HA has a stronger catalytic ability for the conversion of high-order polysulfides. When the battery is further discharged to 2.2 V, the absorbance on CNT The absorbance continued to increase, while the The absorbance gradually decreases and reaches a minimum value at the final discharge state, indicating that HA can convert low-order polysulfides to lower-order polysulfides (Li2S2 / Li2S) to a greater extent. These results confirm that the intrinsic structure and properties of CNT / HA can more efficiently catalyze the solid-liquid-solid conversion of sulfur compared to CNT.
[0124] 6.3 Effect of HA on Lithium Ion Transport
[0125] Li + Diffusion is another important factor affecting the sulfur conversion reaction rate. In order to verify the electrode kinetics of HA, especially the Li + In order to investigate the effect of diffusion, the CV curves of CNT-S / HA and CNT-S cathode at different scan rates were recorded. Figure 18 As shown, all reduction and oxidation peaks correspond to the typical multi-step sulfur conversion reactions between Li2S8 and Li2S. It is worth noting that the CNT-S / HA cathode shows a stronger peak current and smaller polarization than the CNT-S cathode, indicating that HA significantly promotes the redox kinetics of polysulfides.
[0126] In addition, the Li of the two systems can be estimated by the classic Randles-Sevcik equation (Eq. 1) using CV at different scan rates. + The diffusion coefficient (DLi + ). This equation shows the peak current intensity (I p ) and the scan rate (ν 0.5 ) has a linear relationship with the square root of p is the peak current, n is the number of electron transfers (n = 2), S is the geometric area of the electrode (1.53 cm 2 ), D Li + For Li + Diffusion coefficient, C is the Li in the electrolyte + Concentration (0.001 mol cm -3 ), v is the scanning rate. Since n, S and C are known data, we can use I p is the horizontal axis, v 0.5 The slope of the graph with the vertical axis reflects the D Li + .like Figure 23 As shown in the figure, the slope of the CNT-S / HA cathode is higher than that of the CNT-S cathode during the entire sulfur oxygen reduction process, indicating that the Li + The diffusion rate of HA double helix is faster. + The applicant measured the CV of HA monomer mixture (i.e. D-GLCA+GLcNAc, not forming a double helix structure) at different scan rates and obtained the corresponding D Li + .from Figure 23 It can be clearly seen that compared with the CNT-S / HA cathode, the CNT-S / D-GLCA / GLcNAc cathode exhibits a slower Li + Diffusion, showing that the unique double helix structure of HA accelerates Li + played an important role in diffusion.
[0127] GITT can also be used to evaluate D Li + , this method is based on a simplified Fick's second law. Figure 24 The GITT curves of CNT-S / HA, CNT-S / D-GLCA / GLcNAc and CNT-S cathode are presented. Figure 24 and Figure 25 It can be seen that among the three cathodes, the CNT-S / HA cathode shows lower electrochemical equilibrium polarization voltage (E1=117.8 mV), actual polarization voltage (E2=189.1 mV), and nucleation growth overvoltage (E3=34.7 mV), indicating that HA significantly improves the sulfur reaction kinetics. Figure 26Shows the D calculated by GITT curve Li + It can be clearly seen that the CNT-S / HA cathode shows a higher D value than the CNT-S cathode and CNT-S / D-GLCA / GLcNAc cathode during the charge and discharge process. Li + The CV results at different scan rates showed the same conclusion, that is, the double helix structure of HA promoted the Li + diffusion.
[0128] The applicant then performed MD calculations to simulate the Li + Diffusion dynamics. Figure 27 As shown, D in the double helical HA model Li + The values were always higher than those in the D-GLCA / GLcNAc model. Li + This is consistent with the above experimental results. All the findings fully prove that the double helix structure of HA plays an important role in accelerating Li + Optimal role in diffusion dynamics.
[0129] 6.4 Battery Performance
[0130] The above experiments have proved that HA not only has good adsorption of polysulfides and electrolytes, but also accelerates the sulfur conversion kinetics and Li + Therefore, the CNT-S / HA cathode (sulfur content of 80 wt% and sulfur loading of approximately 1.0 mg cm) was evaluated in CR2025 coin cells. -2 , E / S is 20 μL mg -1 ) of battery performance. Figure 28 The rate performance of lithium-sulfur batteries with different HA addition amounts was demonstrated, and it was found that 1% was the optimal HA addition ratio.
[0131] Figure 29 The electrochemical performance of CNT-S / HA and CNT-S cathodes at different rates was demonstrated. The CNT-S / HA cathode had a high capacity of 1493 mAh g at 0.2 C. -1 The initial specific capacity (1 C = 1675 mA g -1 ), equivalent to 89.13% of the theoretical capacity of sulfur, showing a high sulfur utilization rate. When the rate gradually increased from 0.2 C to 0.5 C, 1 C, 1.5 C, 2 C, 3 C and 4 C, the capacities were 1493, 1062, 975, 923, 882, 837 and 779 mAh g, respectively. -1 Even when the rate is increased to 5 C, the CNT-S / HA cathode can still maintain 714 mAh g-1 In comparison, the CNT-S cathode has a specific capacity of 25 mAhg at 5 C. -1 When the rate suddenly returns to 0.2 C, the discharge capacity of the CNT-S / HA cathode can be well recovered, showing that the HA-modified cathode has excellent sulfur conversion catalytic activity and reversible lithium-sulfur electrochemical reaction performance. In contrast, the CNT-S can only recover to 717 mAh g -1 The excellent rate performance of CNT-S / HA cathode is the key to the + The direct result of the accelerated transport and sulfur catalytic conversion kinetics. Figure 30 shows that at different rates, the CNT-S / HA battery always has a smaller polarization voltage, which further confirms that HA has stronger catalytic and Li + Ion transport capacity.
[0132] like Figure 31 As shown, the CNT-S / HA cathode has a capacity of 985 mAh g at 1 C. -1 It has an ultra-high initial capacity and can still maintain 688 mAh g after 1500 cycles. -1 The capacity retention rate reached 69.8%, and the single-cycle decay rate was only 0.02%, showing excellent cycling stability. In contrast, the initial capacity of the CNT-S cathode at 1 C was only 970.02 mAh g -1 , and experienced severe capacity decay after only 1000 cycles. The long-cycle performance and stability were not comparable to those of batteries containing HA catalysts.
[0133] In order to further verify the feasibility of HA in actual lithium-sulfur battery (high sulfur content, lean electrolyte usage), the CNT-S / HA cathode was tested at high sulfur loading (8 mg cm -2 ) and low E / S ratio (5 μL mg -1 ) under the cycle performance. Figure 32 As shown in (a) and (b), the CNT-S / HA cathode can be stably cycled 98 times at 0.2 C and maintain 6.74 mAh cm -2 The areal capacity of the HA-modified battery (capacity retention rate: 92.38%) is better than that of the CNT-S battery (capacity retention rate after 46 cycles is only 38.7%). The smaller amount of electrolyte used will undoubtedly cause the battery to produce a larger polarization at a relatively high rate due to the slower electron and ion transport. It is worth noting that even under the condition of poor electrolyte, the HA-modified battery still has a clear charge and discharge platform and a small polarization (ΔE=0.19 mV, close to Figure 30 The polarization voltage of a battery with sufficient electrolyte in a medium reveals the excellent catalytic activity and electrolyte adsorption capacity of HA.
[0134] In addition, the applicant also assembled a 1.5 Ah soft pack battery using CNT-S / HA cathode ( Figure 32 (c) Under more stringent conditions (areal sulfur loading of 8 mg cm -2 , E / S ratio was 3 μL mg -1 ).like Figure 32 As shown in Figure d, the battery has a capacity of 11.76 mAh cm in the first cycle. -2 The reversible capacity and initial specific energy density are as high as 409 Wh kg -1 , and was able to perform 76 stable cycles at 0.1 C. Due to its high energy density, the battery successfully powered a small drone for 20 minutes, which is about four times longer than a traditional lithium-ion battery of the same weight, which can only power it for about 3-5 minutes. This shows that HA can reduce electrolyte consumption, thereby improving battery performance. Compared with high-performance lithium-sulfur batteries ( Figure 32 (d) It is obvious that the applicant's battery is more competitive in overall performance.
[0135] The foregoing description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Those skilled in the art will readily appreciate that various modifications and variations of the present invention are possible. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention are intended to be within the scope of protection of the present invention.
Claims
1. Application of hyaluronic acid in the preparation of lithium-sulfur battery cathode composite material, characterized in that: The lithium-sulfur battery is a lean electrolyte lithium-sulfur battery, and the lean electrolyte condition is: sulfur loading> 4 mg·cm -2 、Electrolyte / sulfur<5 μL·mg -1 , E / S ratio <5 μL·mg -1 First, hyaluronic acid HA, carbon nanotubes CNT and polyvinylidene fluoride PVDF are added to 1-methyl-2-pyrrolidone NMP and ultrasonically shaken for 1 hour to make them uniformly dispersed in NMP. Then, the CNT-S composite material obtained by compounding CNT and sulfur powder is added and stirred evenly to obtain a slurry. The slurry is then evenly coated on aluminum foil and vacuum dried to obtain a cathode composite material. Among them, the mass ratio of HA, CNT, PVDF and CNT-S composite materials is 0.2~4:14.8~11:5:
80.
2. The use according to claim 1, characterized in that The CNT-S composite material is prepared by the following method: first, CNT and sulfur powder are mixed in a mass ratio of 2:8 and ground for 30 minutes, then dried, cooled, and sieved.
3. The use according to claim 1, characterized in that The cathode composite material is used to prepare a composite cathode of a lithium-sulfur battery.
4. The use according to claim 3, characterized in that The cathode composite material is used for preparing lithium-sulfur batteries.
5. The use according to claim 4, characterized in that The lithium-sulfur battery is a button cell or a soft pack cell.
6. The use according to claim 4, characterized in that A lithium-sulfur battery is obtained by assembling a composite cathode made of hyaluronic acid with a separator, a metal lithium anode, and an electrolyte.
Citation Information
Patent Citations
Binding agent for lithium-sulfur battery and preparation method thereof and lithium-sulfur battery positive electrode
CN108155383A